2019
DOI: 10.1007/s00213-019-05367-0
|View full text |Cite
|
Sign up to set email alerts
|

mGlu5 in GABAergic neurons modulates spontaneous and psychostimulant-induced locomotor activity

Abstract: Rationale-A role of group I metabotropic glutamate receptor 5 (mGlu5) in regulating spontaneous locomotion and psychostimulant-induced hyperactivity has been proposed.Objectives-This study aims to determine if mGlu5 in GABAergic neurons regulates spontaneous or psychostimulant-induced locomotion.Methods-We generated mice specifically lacking mGlu5 in forebrain GABAergic neuron by crossing DLX-Cre mice with mGlu5 flox/flox mice to generate DLX-mGlu5 KO mice. The locomotion of adult mice was examined in the open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 112 publications
3
6
0
Order By: Relevance
“…They reported genetic associations between genotypes and the grazing behaviours of home range and movement tortuosity, with a trend towards association with elevation range and horizontal distance travelled. These findings, together with the earlier study of Bailey et al ( 2015 ) and the reported associations of GRM5 expression variation with activity levels and exploratory behaviours in animal models (Bakker and Oostra 2003 ; Jew et al 2013 ; Wu et al 2020 ), support the relevance of GRM5 as a predictor of grazing personality behaviours in beef cattle.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…They reported genetic associations between genotypes and the grazing behaviours of home range and movement tortuosity, with a trend towards association with elevation range and horizontal distance travelled. These findings, together with the earlier study of Bailey et al ( 2015 ) and the reported associations of GRM5 expression variation with activity levels and exploratory behaviours in animal models (Bakker and Oostra 2003 ; Jew et al 2013 ; Wu et al 2020 ), support the relevance of GRM5 as a predictor of grazing personality behaviours in beef cattle.…”
Section: Introductionsupporting
confidence: 71%
“…The broad array of 35 variables were chosen based on their use in previous studies (Bailey and Provenza 2008 ; Bailey et al 2006 ; Browning et al 2018 ; Gillen et al 1984 ; Senft 1989 ; Senft et al 1983 ). Over the 15 consecutive days of GPS-based monitoring, the individual cow measurements were aggregated into daily mean values and coefficients of variation (CV) calculated using the ‘summary()’ function of ‘dplyr’ R package (Wickham et al 2021 ). Variables that were abnormally distributed were excluded from further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Mobility was tested in a custom-made testing arena placed on the floor, with dimensions of 40 (length) × 40 (width) × 38 (height) cm. Mice were allowed to explore the arena freely for 10 min [ 26 , 27 , 28 ]. The experiment was video-recorded and tracked using ANY-maze software (Stoelting Co., Dublin, Ireland).…”
Section: Methodsmentioning
confidence: 99%
“…In the behavioural context, Fu et al [64] illustrated that the effects of silent mutations on Drosophila circadian rhythm and thus, its potential implications on the regulation of animal daily and seasonal behaviours in general, which could apply Moreno García et al Journal of Animal Science and Biotechnology (2022) 13:111 to free-range cattle in steep and rugged terrain [65]. Considering the previously reported associations of GRM5 with behaviour, movement and cognitive abilities in several animal species [15,[17][18][19]21], the variants of bovine GRM5 reported here are notable, because of their potential for use in cattle selection programmes that could target particular grazing patterns and cattle distribution in rangelands.…”
Section: Variation In the Bovine Grm5 Genementioning
confidence: 99%
“…Jew's et al results showed direct association between GRM5 and locomotor reactivity to a novel environment, increased and decreased exploratory behaviour and, activity levels of mice. Subsequently, Wu et al [19] reported that GRM5 in the forebrain GABAergic neurons of mice modulated locomotor activity, and in this way it affected their horizontal and vertical distances travelled and the time spent moving. These authors reported that mice with genotypic variation in the glutamate metabotropic receptor 5 gene (GRM5) displayed different levels of activity in familiar and unfamiliar environments.…”
Section: Introductionmentioning
confidence: 99%